Influence of Parental Education Level and Involvement on Students’ Academic Achievement in Nsukka Local Government Area, Enugu State, Nigeria - Okafor, Ikechukwu Giveson; Eze, Maureen Ugonne; Ihediwa, Ernest (Universal Education Jurnal Teaching and Learning, 2026)
This paper investigated the influence of parental educational level and parental involvement in the child’s education on students’ academic achievement in the Nsukka Local Government Area (LGA) of Enugu State in South-East Nigeria. Two research questions and two hypotheses were formulated for the study. The study adopted a descriptive design. The sample size comprised 384 grade 9 (JSS3) students in junior secondary schools in Southeast Nigeria. The instruments for data collection were a questionnaire on parental involvement in students’ education and a test instrument covering English Language, Mathematics, and Civic Education components. The data collected for the study were analysed using mean, standard deviation, and t-test. Findings revealed that parental education level significantly influenced students’ academic achievement; students whose parents have lower levels of education performed better than their counterparts in the achievement test. On the other hand, students whose parents were more involved in their education scored higher than those whose parents were less involved, although the mean difference was not statistically significant. The study concluded with a recommendation that schools should encourage parents to be actively involved in their children’s education, such as volunteering in the classroom or attending parent-teacher conferences, as well as home tutoring.